BALTIC ETHNOCRACIES BETWEEN RUSSIA AND THE EU: IN SEARCH OF CONSENSUS UNDER CONDITIONS OF THE ECONOMIC CRISIS - V. V. Vorotnikov (Vestnik MGIMO-Universiteta)
The economic crisis fueled contradictions among the parties and weakened public support of internal and external policies of the Baltic states (Lithuania, Latvia, Estonia). Natural necessity to abandon previous one-sided Euro-Atlantic foreign political and foreign economic orientation in favor of more balanced approach towards relations with Eastern neighbours (primarily with Russia) has become the issue of key importance that turned out to be a stumbling block for main political parties (ruling parties, opposition, so called ‚Russian‘ parties) in the Baltic states. The attitude to this problem became crucial during recent political crisis in Latvia, whereas in Lithuania and Estonia it led to changing rhetoric on foreign political issues by opposition parties. It is possible to nominally define the political situation in Lithuania as partisan consensus, whereas in Latvia and Estonia foreign political strategies complicated by unresolved domestic ethnic and language minorities problems are a battlegroud for ruling right-wing conservative coalitions and social-democratic oppositions. So, main social and political forces in the Baltic states faced the task to find a new consensus on foreign political issues in order to efficiently develop national economies under the conditions of financial economic turbulence in the EU and worldwide as well as to support social unity.